Literature Review: Cost Effectiveness Analysis Xpert MTB/RIF dibandingkan dengan Sputum Smear Microscopy untuk Diagnosis Tuberkulosis di Indonesia - Putri, Linda Wahyuni; Hartono, Budi (Lembaga Penerbitan Universitas Esa Unggul, 2023)
Abstract Indonesia is the third most TB-prevalent country in the world after India and China. Sputum Smear Microscopy (SSM) is the most commonly used Tuberculosis test in developing countries due to its relatively low unit cost per test but low sensitivity. The World Health Organization recommends using Xpert MTB/RIF as a TB test because it has higher sensitivity and specificity and a shorter time to obtain results. This paper evaluates the cost-effectiveness analysis of Xpert MTB/RIF and Sputum Smear Microscopy in Indonesia. The search for scientific articles was conducted by keyword search through Google Scholar, PubMed, and Elsevier. The keywords used were related to